ANALYSIS OF SERVICE QUALITY DIMENSIONS TOWARDS CUSTOMER SATISFACTION AT BPJS EMPLOYMENT IN MEDAN BRANCH OFFICE - Syumantra, Rhama Fahrezy; Aslami, Nuri (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
This study aims to analyze and identify how to analyze the dimensions of service quality to BPJS customer satisfaction. The research was carried out on the BPJS Employment Office in Medan. The research is a qualitative research approach with a field research strategy. The data collection techniques used in this study were observation techniques, interviews and literature reviews which were carried out by observing and identifying the workings and quality of services received by BPJS Employment customers during the internship activities carried out as well as with interview techniques with several customers and employees of BPJS Employment as resource persons. This study was carried out for 3 weeks during the internship, namely from February 2 to February 22, 2022. The results of analysis according to aspects of service quality shows that customer satisfaction can be influenced by the existence of five aspects of service quality, namely reliability, responsiveness, safety, empathy, and concrete increases. Therefore, the higher the quality of service provided, the better the customer satisfaction. Customer expectations can affect overall performance, attitude, and reputation in the long run.